Vindkraftens påverkan på lokalsamhället : en fallstudie - Wiking, Carl (SLU/Dept. of Urban and Rural Development, 2011)
The purpose of this thesis is to investigate how a local community, and those who dwell within its borders, are affected when a large scale windmill park is planned in its immediate vicinity. I have used a qualitative approach and conducted semi structured interviews to gather empirical data. The study took place in a small Swedish village named Svartnäs, situated in the region Dalarna.